Electro‐Active and Photo‐Active Vanadium Oxide Nanowire Thermo‐Hygroscopic Actuators for Kirigami Pop‐up. Issue 23 (24th October 2021) - Tabassian, Rassoul; Mahato, Manmatha; Nam, Sanghee; Nguyen, Van Hiep; Rajabi‐Abhari, Araz; Oh, Il‐Kwon
Abstract: Emerging technologies such as soft robotics, active biomedical devices, wearable electronics, haptic feedback systems, and healthcare systems require high‐fidelity soft actuators showing reliable responses under multi‐stimuli. In this study, the authors report an electro‐active and photo‐active soft actuator based on a vanadium oxide nanowire (VONW) hybrid film with greatly improved actuation performances. The VONWs directly grown on a cellulose fiber network increase the surface area up to 30‐fold and boost the hydrophilicity owing to the presence of oxygen‐rich functional groups in the nanowire surfaces. Taking advantage of the high surface area and hydrophilicity of VONWs, a soft thermo‐hygroscopic VONW actuator capable of being controlled by both light and electric sources shows greatly enhanced actuation deformation by almost 70% and increased actuation speed over 3 times during natural convection cooling. Most importantly, the proposed VONW actuator exhibits a remarkably improved blocking force of up to 200% compared with a bare paper actuator under light stimulation, allowing them to realize a complex kirigami pop‐up and to accomplish repeatable shape transformation from a 2D planar surface to a 3D configuration. Abstract : An electro‐active and photo‐active soft actuator based on a vanadium oxide nanowire (VONW) hybrid film is developed with greatly improved actuation performances. The VONWs directly grown on a cellulose fiber network increase the surface area up to 30‐fold and boost the hydrophilicity owing to the presence of oxygen‐rich functional groups in the nanowire surfaces, resulting in superior thermo‐hygroscopic soft actuation.